TRAINING ON THE PRODUCTION OF NATURAL DISHWASHING SOAP FOR STUDENTS AT MA MUHAMMADIYAH I MALANG - Ningsih, Gumoyo Mumpuni; Rasyid, Harun; Baroh, Istis (LPPM Univ. Ibn Khaldun Bogor, 2025)
Based on the situation analysis and interviews with the school of MA Muhammadiyah I Malang, Tlogomas Village, Malang City, it was found that many teachers want to equip students with entrepreneurial skills, especially for those who do not continue to college. One of the potential skills to be developed is the manufacture of natural-based dish soap. Therefore, training was conducted in October 2024 to provide practical skills that can be applied in the business world. This training uses counseling and hands-on methods, where students gain knowledge and the opportunity to practice making liquid dish soap. The results of the service showed that this activity went very well and smoothly. The school welcomed this program because it is relevant to the subject of entrepreneurship. The students, both male and female, showed high enthusiasm in participating in the training. All participants attended 100%, experienced an increase in knowledge and skills, and 60% of them were interested in entrepreneurship in this field. In conclusion, the training was effective in improving students' entrepreneurship skills and it is hoped that it can be further supported with capital assistance for those who want to start a business.